Drug Abuse and Women’s Involvement in Drug-related Crimes in Bangladesh and Indonesia: A Comparative Analysis - Rahman, Md. Masudur; Kabir, Md. Humaun (Universitas Muhammadiyah Yogyakarta, 2025)
This article attempts to examine in what manner women are involved in drug-related crimes and explores the factors and scenarios of drug abuse to compare two Southeast Asian countries, Bangladesh and Indonesia. Drug abuse and drug peddling are an uprising phenomenon in recent society. Drugs are scattered in every corner in all the divisions in Bangladesh. Additionally, Indonesia has the highest rates of women’s drug addiction. Women’s involvement in drug-related crime is not a new phenomenon. Studies found that not enough easy access to drugs and the availability of consumers due to curiosity are the main causes of women’s involvement in drug peddling. This is a mixed-method study based on secondary analysis, which includes numeric data related to drug abuse and women’s involvement. Some case studies are also captured where study findings portray the increasing status of drug abuse, including women’s involvement. The theory of deviant behaviour is also used to connect with the findings. This study recommends controlling drug abuse among all addicted people, especially women’s involvement.